2022
DOI: 10.1186/s40634-022-00537-0
|View full text |Cite
|
Sign up to set email alerts
|

The composition of cell-based therapies obtained from point-of-care devices/systems which mechanically dissociate lipoaspirate: a scoping review of the literature

Abstract: Purpose Cell-based therapies using lipoaspirate are gaining popularity in orthopaedics due to their hypothesised regenerative potential. Several ‘point-of-care’ lipoaspirate-processing devices/systems have become available to isolate cells for therapeutic use, with published evidence reporting their clinical relevance. However, few studies have analysed the composition of their ‘minimally-manipulated’ cellular products in parallel, information that is vital to understand the mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
(228 reference statements)
1
7
1
Order By: Relevance
“…The present study was able to obtain an average of 1.3 ± 0.2 x107 cells/mL, that is, about one thousand more cells per mL. Also in the study by Liu et al 2022, ten articles reported cell viability (the measure of live cells ranging from 60 to 98%) [12]. In the present study, cell viability was 99.5± 0.3%, which is higher than the average of published articles.…”
Section: Vol 3 Iss 4 Year 2022contrasting
confidence: 44%
See 4 more Smart Citations
“…The present study was able to obtain an average of 1.3 ± 0.2 x107 cells/mL, that is, about one thousand more cells per mL. Also in the study by Liu et al 2022, ten articles reported cell viability (the measure of live cells ranging from 60 to 98%) [12]. In the present study, cell viability was 99.5± 0.3%, which is higher than the average of published articles.…”
Section: Vol 3 Iss 4 Year 2022contrasting
confidence: 44%
“…The 15 studies were analyzed and published by the authors Liu et al 2022 through a systematic review [12]. All studies reported the cell concentration (number of cells regardless of phenotype per milliliter of liposuction) for their devices/systems (range 0.005-21×106) [12]. The present study was able to obtain an average of 1.3 ± 0.2 x107 cells/mL, that is, about one thousand more cells per mL.…”
Section: Vol 3 Iss 4 Year 2022mentioning
confidence: 78%
See 3 more Smart Citations